DIVERSITY AND COMMUNITY STRUCTURE OF MACROALGAE AT KOH TAEN, HAAD KHANOM-MU KOH TALE TAI, MARINE NATIONAL PARK, NAKHON SI THAMMARAT PROVINCE, THAILAND - Prathep, Anchana; Darakrai, Anuchit; Tantiprapas, Piyalap; Mayakun, Jaruwan; Thongroy, Pimonrat; Wichachucherd, Bongkot; Sinutok, Sutinee (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
The diversity and community structure of macroalgae at Koh Taen, Haad Khanom-Mu Koh Tale Tai, marine National Park, Nakhon Si Thammarat Province, Thailand were investigated from 1st- 5th October 2005 (preliminary survey). Out of a total of 41 species: 15 species each of green and red algae, 9 species of brown algae and 2 species of blue green algae were found. In the area, subsequently four sites were established for monitoring. Quadrat sampling was employed to assess the abundance of macroalgae. In total sixty quadrats were monitored each month from October 2005 to April 2007. We report the variations of diversity and abundance of macroalgae among sites and seasons and speculate about what might cause such variations.